Towards a phylogeny of the Tenebrionoidea (Coleoptera) - Gunter, Nicole L; Levkaničová, Zuzana; Weir, Tom H; Ślipiński, Adam; Cameron, Stephen L; Bocak, Ladislav (Molecular phylogenetics and evolution, 2014)
The phylogenetic relationships of the beetle superfamily Tenebrionoidea are investigated using the most comprehensive genetic data set compiled to date. With ∼34,000 described species in approximately 1250 genera and 28 families, Tenebrionoidea represent one of the most diverse and species-rich superfamilies of beetles. The interfamilial relationships of the Tenebrionoidea are poorly known; previous morphological and molecular phylogenies recovered few well-supported and often conflicting relationships between families. Here we present a molecular phylogeny of Tenebrionoidea based on genes commonly used to resolve family and superfamily-level phylogenies of beetles (18S, 28S, 16S, 12S, tRNA Val and COI). The alignment spanned over 6.5KB of DNA sequence and over 300 tenebrionoid genera from 24 of the 28 families were sampled. Maximum Likelihood and Bayesian analysis could not resolve deeper level divergences within the superfamily and very few relationships between families were supported. Increasing gene coverage in the alignment by removing taxa with missing data did not improve clade support but when rogue taxa were removed increased resolution was recovered. Investigation of signal strength suggested conflicting phylogenetic signal was present in the standard genes used for beetle phylogenetics, even when rogue taxa were removed. Our study of Tenebrionoidea highlights that even with relatively comprehensive taxon sampling within a lineage, this standard set of genes is unable to resolve relationships within this superfamily.
Keywords: Coleoptera; Anthicidae; Genes, Insect; fylogeneze; Likelihood Functions; Signal strength; Bayesova věta; Animals; Rogue taxa; Lymexyloidea; Sequence Analysis, DNA; Zopheridae; zvířata; Tenebrionidae; Bayes Theorem; Phylogeny; hmyzí geny; sekvenční analýza DNA; brouci; pravděpodobnostní funkce